Neonatal Seizure Characteristics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Seizure characteristics in 32 neonates were studied prospectively using prolonged video/EEG recording at the Prince of Wales Children's Hospital, Sydney, Australia.